The Feasibility and Effectiveness of High-Level Thinking Tests on Virus to Mapping The Ability of Prospective Science Teacher (Introduction Study on The Development of Integrated Learning Models) - Kusumadani, Annur Indra; Rahardjo, Sentot Budi; Yamtinah, Sri; Prayitno, Baskoro Adi (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
This research aims to determine the feasibility and effectiveness of a higher - order thinking test developed on material of virus. The test instrument developed was aimed at mapping the ability of prospective science teacher in the preliminary study of developing an integrated learning model. This research is a Research and Development referring to Borg and Gall ( 1989) with 10 stages of research, namely : (1) Initial research and data collection , (2) Planning , (3) Initial product manufacture , (4) Initial trial (expert validation) , (5) Initial product improvement , (6) Test field trial , (7) Operational product improvement , (8) Operational field test (effectiveness test/external validity test) , (9) Final product revision, and (10) Dissemination. The research involved the following experimental subjects : (1) The initial trial involved virus material experts, research and education evaluation experts ; (2) The small group trial involved 36 student teacher candidates at the University of Muhammadiyah Surakarta for the 2020/2021 academic year; (3) The large group trial involved 60 student teacher candidates at the University of Muhammadiyah Surakarta for the 2020/2021 academic year ; and (4) an operational field test (effectiveness test/external validity test) involving 30 teacher candidates at the Muhammadiyah University of Surakarta for the 2020/2021 academic year. The data analysis techniques used were the validity of AIken at the validation stage, item test analysis in the field trial and Pearson correlation analysis at the operational /effectiveness field test stage. The final results of this research are computer-assisted higher order thinking test with 8 questions of higher order thinking on virus material that has strong internal validity with an Aiken validity index of more than 0.73 ( 0.84 to 0.92 ), reliability coefficient 0.814 > 0.213 (r table ) which means high reliability, difficulty index of 0.17 (difficult) to 0.455 (medium), and discriminant index (differentiation power) of 0.2 (enough) to 0.745 (good). External validity/effectiveness is 0.626 (strong enough) to 0.831 (strong) which is the correlation of higher order thinking test results developed with other higher-order thinking tests on virus. The conclusion of this research is that the developed test instrument is feasible and effective to measure the higher order thinking ability of virus.